Effectiveness of an Educational Program in Nursing in the Self-care of Patients with Heart Failure : Randomized Controlled Trial (2012)
ABSTRACT: Unblinded randomized controlled clinical trial to evaluate the effectiveness of an educational program in nursing (educational meetings, home visits, telenursing and a printed book) in the improvement of self-care behaviors in patients with heart failure was evaluated. Thirty-three people participated in the intervention group and thirty in the control group. At the beginning and at the end of the study (ninth month), Nancy Artinian’s heart failure self-care behaviors scale was applied to assess the level of self-care. 66.0% of the intervention group versus 26.6% of the control group improved the self-care score by at least 20% (p<0.001). The number needed to treat was 2.5. The findings suggest that the educational intervention has beneficial effects on the self-care behaviors of people with heart failure.